2017
DOI: 10.3389/fmicb.2017.01739
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Antibiotic Susceptibility and Genotype in Mycobacterium abscessus Clinical Isolates

Abstract: This study aimed to determine the antibiotic susceptibility and resistance related genotypes of Mycobacterium abscessus. One hundred sixty-two clinical isolates were collected. Genomic data were obtained by whole genome sequencing. Single nucleotide polymorphism (SNP) analysis was conducted using the NCBI GenBank database and BLAST algorithm. The following genes were of interest: erm(41), rrl and rrs. Erm(41) was further divided into 3 sequevars: erm(41)C28, erm(41)T28, and M type [erm(41) with deletions in nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 31 publications
2
27
2
Order By: Relevance
“…On the other hand, three M. massiliense isolates (MAS04: >16μg/ml, MAS06: >16μg/ml, MAS10: >16μg/ml) exhibited inducible resistance to CLR and AZM on the 14 th day. This is contrast with previous studies (Kim et al , 2015; Koh et al , 2010) which demonstrated that inducible resistance to CLR was only present in M. abscessus and not in M. massiliense. Nevertheless, our results support the findings of Li et al .…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…On the other hand, three M. massiliense isolates (MAS04: >16μg/ml, MAS06: >16μg/ml, MAS10: >16μg/ml) exhibited inducible resistance to CLR and AZM on the 14 th day. This is contrast with previous studies (Kim et al , 2015; Koh et al , 2010) which demonstrated that inducible resistance to CLR was only present in M. abscessus and not in M. massiliense. Nevertheless, our results support the findings of Li et al .…”
Section: Resultscontrasting
confidence: 99%
“…Susceptibility rates of M. abscessus complex isolates in the present study showed that MXF has better in vitro activity against M. abscessus (81.8% susceptible) and M. massiliense (60% susceptible) compared to CIP against M. abscessus (9.1% susceptible) and M. massiliense (20% susceptible). This is consistent with other studies showing that MXF has better in vitro activity against M. abscessus and M. massiliense compared to CIP (Kim et al , 2015; Lee et al , 2014; Koh et al , 2010). On the other hand, DOX was found to be more potent against M. abscessus (72.7% susceptible) isolates compared to its activity against M. massiliense (10% susceptible).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The anti- M. abscessus activity of imipenem in vitro is variable; bacterial resistance was over 60% in some studies (12, 17, 18). Imipenem was efficacious, however, in treating pulmonary M. abscessus disease in our study.…”
Section: Discussionmentioning
confidence: 99%